Fluid-controlled tunable infrared filtering in hollow plasmonic nanofin cavities. (13th September 2016) - Ho, Ya-Lun; Abasaki, Minoru; Yin, Shichen; Liu, Xin; Delaunay, Jean-Jacques
Abstract: Subwavelength structures sustaining surface plasmons have been employed in numerous fields due to their small size and ability to manipulate light beyond the diffraction limit. Light filtering using small-size plasmonic devices is a promising means of portable spectroscopy for purposes such as on-site chemical analyses. However, most plasmonic filters can only tune the resonance band by modifying the geometry of the structure or changing the incident light angle. Here, we present a plasmonic nanofin-cavity structure having a narrow band with its resonance wavelength controlled by varying the fluid in the hollow cavities of the filter. Control of the narrow-band resonance is realized over a wide range because of the coupling between the stationary surface plasmons generated from the nanofin-cavity mode and the propagating surface plasmons. The hollow cavity design enables fluid to be easily injected and removed, so that the filtered band can be controlled without the need for a complex and bulky structure or application of an external voltage.